Når døde børn er livets gave - Unisex moderskab og organdonation i USA - Jensen, Anja Marie Bornø (Kvinder, Køn & Forskning, 2008)
Dead children as ";the gift of life";. Unisex motherhood and organ donation in America The focus of this article is how American women, especially mothers of organ donors dominate organizational support efforts for donor families, the implications this has for men, and the many new understandings of motherhood this medical context gives rise to. Based on anthropological field studies from the US, this article analyses the efforts of American organ organizations to support and comfort families in the time after the organ donation and explores the limited options for men to engage in this interaction, except by acting like ‘mothers'. By exploring how women speak about donation and engage in many different social relations to organ recipients and others, this article give rise to new perceptions of motherhood and discusses how gender is acted out in this particular field.